The Impact of Information Communication Technology Developments in The Indigenous Law Community - Romana, Francisca; Saptomo, Ade; Mardina, Debi; Siska, Siska; Naning, Theresia (Syntax Corporation, 2024)
The development of information and communication technology (ICT) always has an impact on changes in human paradigms, both positive and negative. This change in the human paradigm will conflict or not conflict with Indigenous law which is the guideline for the Indigenous law community. The question is, to what extent are the boundaries that guide Indigenous law community that this paradigm change is or is not in conflict with Indigenous law that applies to Indigenous law community, thereby resulting in restrictions on the use of ICT by Indigenous law community? In this research, there are two case studies, namely the development of ICT, which is considered contrary to Indigenous law and the acceptance of ICT development in the Indigenous law community of Baduy Dalam, Baduy Luar, and Kasepuhan Ciptagelar Sukabumi. This research aims to examine the impact of ICT developments on the paradigm of the Indigenous law community of Baduy Dalam, Baduy Luar, and Kasepuhan Ciptagelar so that the results of this research can be used as a reference for the government to determine appropriate regulations for implementing digital transformation programs for Indigenous law community.